2021
DOI: 10.3389/fcell.2021.649433
|View full text |Cite
|
Sign up to set email alerts
|

The Wdr1-LIMK-Cofilin Axis Controls B Cell Antigen Receptor-Induced Actin Remodeling and Signaling at the Immune Synapse

Abstract: When B cells encounter membrane-bound antigens, the formation and coalescence of B cell antigen receptor (BCR) microclusters amplifies BCR signaling. The ability of B cells to probe the surface of antigen-presenting cells (APCs) and respond to APC-bound antigens requires remodeling of the actin cytoskeleton. Initial BCR signaling stimulates actin-related protein (Arp) 2/3 complex-dependent actin polymerization, which drives B cell spreading as well as the centripetal movement and coalescence of BCR microcluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…Loss of INPP5B dramatically impaired cell spreading, which is also likely to contribute to the reduced BCR clustering that was observed. This effect is also due to a failure to hydrolyze PI(4,5)P 2 , and again cofilin and additional PI(4,5)P 2 -binding regulatory factors are likely to be involved ( Bolger-Munro et al, 2021 ; Freeman et al, 2011 ; Li et al, 2018 ; Tolar, 2017 ). Cell spreading involves constant spatially controlled turnover of the actin network, and these factors are required to undergo rounds of activation and inactivation to allow actin remodeling to occur, driven by constant PI(4,5)P 2 turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of INPP5B dramatically impaired cell spreading, which is also likely to contribute to the reduced BCR clustering that was observed. This effect is also due to a failure to hydrolyze PI(4,5)P 2 , and again cofilin and additional PI(4,5)P 2 -binding regulatory factors are likely to be involved ( Bolger-Munro et al, 2021 ; Freeman et al, 2011 ; Li et al, 2018 ; Tolar, 2017 ). Cell spreading involves constant spatially controlled turnover of the actin network, and these factors are required to undergo rounds of activation and inactivation to allow actin remodeling to occur, driven by constant PI(4,5)P 2 turnover.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CLNK (506 kb from chr3:assocA/effect variant in LR and 367 kb from chr3:assocB) encodes a crucial signaling component of high-affinity IgE receptor induced mast cell degranulation 72 . WDR1 (98 kb from chr3:assocB) is involved in actin remodeling required when B cells respond to antigenpresenting cell (APC)-bound antigens 73 . The homeobox transcription factor MSX1 (53 kb from chr3:assocC), together with MSX2 and MOX1, is important for controlling dermal development, epithelial differentiation and proliferation into adulthood 74 , and KLF3 (142 kb from chr3:assocD and 555 kb from chr3:sel) encodes a transcription factor that controls gene expression during epidermal differentiation 75 .…”
Section: Discussionmentioning
confidence: 99%
“…In lamellipodia, the actions of the Arp2/3 complex and cofilin are tightly coupled with cofilin-dependent recycling of actin monomers and Arp2/3 complexes sustaining actin treadmilling (Carlier and Shekhar, 2017). We have shown that cofilin and its co-factor Wdr1 are critical regulators of actin dynamics and organization in B cells, and are important for B cell spreading as well as the actin-dependent amplification of BCR signaling at the immune synapse (Freeman et al, 2011;Bolger-Munro et al, 2021). In contrast to cofilin, capping proteins and their interactors regulate actin monomer depolymerization at the barbed ends of filaments (Edwards et al, 2014).…”
Section: Discussionmentioning
confidence: 99%